2006
DOI: 10.1097/00000542-200606000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Administration Increases Intraoperative Core Temperature by Augmenting Both Metabolic Rate and the Vasoconstriction Threshold

Abstract: Background-We tested the hypothesis that intravenous fructose ameliorates intraoperative hypothermia both by increasing metabolic rate and the vasoconstriction threshold (triggering core temperature)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…5 Interestingly, Mizobe et al reported that infusion of fructose for fasting preoperative surgical patients led to an increase in core temperature compared with those receiving normal saline infusion. 21 This was achieved by increasing oxygen consumption and metabolic rate. The authors postulated that fructose provided metabolic substrate for thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Interestingly, Mizobe et al reported that infusion of fructose for fasting preoperative surgical patients led to an increase in core temperature compared with those receiving normal saline infusion. 21 This was achieved by increasing oxygen consumption and metabolic rate. The authors postulated that fructose provided metabolic substrate for thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in humans have also shown that fructose stimulates de novo lipogenesis and blocks fatty acid oxidation in the liver (13, 6366). Acutely (hours) fructose stimulates thermogenesis and metabolic rate (67, 68), but chronically fructose (days to weeks) has been shown to reduce resting energy expenditure (66). The mechanisms for these effects are discussed below, but it is readily evident how these processes could lead to fat accumulation in the liver and elsewhere.…”
Section: Fructose Effect On Lipogenesis and Fat Oxidationmentioning
confidence: 99%
“…We also reported that preoperative oral amino acid intake contributes to the prevention of intraoperative hypothermia under general anesthesia in rats [10]. Mizobe et al [11] reported that preoperative fructose infusion helped to maintain normothermia by augmenting metabolic heat production and increasing the vasoconstriction threshold.…”
Section: Introductionmentioning
confidence: 59%
“…However, the thermic effect in subjects under general anesthesia was found to be fivefold higher than that in awake individuals [14]. Mizobe et al [11] reported that the metabolic rate is increased by approximately 20% during anesthesia due to the administration of fructose. However, the mechanism underlying this increase has not been elucidated.…”
Section: Discussionmentioning
confidence: 96%